1985
DOI: 10.1111/j.1365-2605.1985.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

The hCG‐induced increase in hormone uptake and interstitial fluid volume in the rat testis is not mediated by steroids, prostaglandins or protein synthesis

Abstract: The possible mediation by steroids, prostaglandins or protein synthesis on the hCG-induced increase in hormone uptake and interstial fluid volume in the rat testis in vivo was studied following a single iv injection of hCG. A high dose of hCG increased its own uptake in the testis and this uptake coincided with an increase in capillary permeability and accumulation of interstial fluid. The possible role of steroids, prostaglandins and protein synthesis in these changes was studied in vivo using aminoglutethimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…Veijola and Rajaniemi (1985) using a smaller, but still effective dose of aminoglutethimide in terms of its steroid synthesis inhibition, found that this drug had no effect on the entry of labelled hCG into the testis, nor on the hCG-induced accumulation of interstitial fluid, supporting our belief that the effects of this drug in our experiments were due to non-specific effects on the animal. Nevertheless, it will be interesting to study the time course of the oestrogen response to hCG, to see whether it corresponds with the vascular response; it would seem more likely to follow the testosterone response.…”
Section: Discussionsupporting
confidence: 73%
“…Veijola and Rajaniemi (1985) using a smaller, but still effective dose of aminoglutethimide in terms of its steroid synthesis inhibition, found that this drug had no effect on the entry of labelled hCG into the testis, nor on the hCG-induced accumulation of interstitial fluid, supporting our belief that the effects of this drug in our experiments were due to non-specific effects on the animal. Nevertheless, it will be interesting to study the time course of the oestrogen response to hCG, to see whether it corresponds with the vascular response; it would seem more likely to follow the testosterone response.…”
Section: Discussionsupporting
confidence: 73%
“…Since PG production regulates changes in vascular permeability and blood flow in other tissues, most notably during inflammation [1], endogenous PG production by the testis also may be involved in maintaining fluid balance and vascular function. Balanced against this, the limited data so far available have not provided any direct evidence for this possibility [17,18]. Finally, while the expression of PTGS2 and nascent PGE 2 production by the developing germ cells may simply prefigure the production of PGs by the mature spermatozoa, this expression pattern of PTGS2 also suggests a potential role for PGs in communication between the spermatogenic cells and the Sertoli cells within the seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 83%
“…Published data suggest that PGs do not play a critical role in the regulation of the testicular vasculature [17,18], but PG production by testicular macrophages may be involved in modulating local immune and inflammatory responses. Several studies have shown that the macrophages of the testis possess reduced inflammatory capacity and may actually play an active role in protecting the developing germ cells by locally suppressing immune responses [19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…We suggested that this hCG-induced increase in tes¬ ticular venular permeability could be mediated at least in part by leukocytes, since elimination of the circulating PMN leukocytes with a specific antisera eliminated the hCG-indued increase in vascular permeability (12). With a few exceptions, almost all studies concerning the effect of hCG on testicular vascular permeability have been using high doses of hCG (7,13). The effect of lower doses has not been tested.…”
mentioning
confidence: 96%
“…While it has been shown that short-term infusion of LH in male rats induced a small decrease in testicular vascular resistance (1), others have failed to detect any changes of LH on testicular circulation (2). On the other hand the hCG-induced increase in total tes¬ ticular blood flow occurring 16-20 h after hCG treatment is well documented (2)(3)(4) as is the hCGindued increment in vascular permeability, measured as changes in testicular interstitial fluid volume, albumin space, and uptake of l25I-hCG oc¬ curring 8-16 h after treatment (3,(5)(6)(7)(8). Further¬ more, results from our group suggest that hCG al¬ ready induces vascular changes in the testes by 4-6 h after treatment, since testicular vasomotion is abolished (8,9), and there is an accumulation of polymorphonuclear (PMN) leukocytes in postcapillary venules and the interstitium (10,11).…”
mentioning
confidence: 98%